PENGARUH KOMUNIKASI, KEPEMIMPINAN, MOTIVASI DAN PELATIHAN TERHADAP KINERJA KARYAWAN PT. NIPSEA PAINT AND CHEMICALS Co. Ltd. - Sembiring, Rasmulia (JURNAL AGRICA, 2015)
This study aims to determine the effect of communication, leadership, motivation and training on the performance of employees at PT. Nipsea Paint and Chemicals Co. Ltd. This research was conducted at PT. Nipsea Paint and Chemicals Co. Ltd. is located at Jl. Yos Sudarso km 8.3 - Tanjung Mulia, Medan. The study population was all employees at PT. Nipsea Paint and Chemicals Co. Ltd. While the sample used in this study using 40 samples. The variables in this study consists of independent variables namely communication (X1), leadership (X2), motivation (X3) and training (X4), while the dependent variable (Y) is the employee's performance. Hypothesis testing used multiple linear regression analysis. The results showed that simultaneous communication (X1), leadership (X2), motivation (X3) and training (X4), a significant effect on employee performance (Y) which is obtained by calculating the value of the F = 140.351 with a significance level of 0.000 is smaller than 0.05. This suggests that an increase of one of the independent variables will further improve employee performance variables. Partially communication variables (X1), leadership (X2), motivation (X3) and training (X4) have a significant effect on performance. Keywords: communication, leadership, motivation, training and performance